2012
DOI: 10.2147/ijn.s28675
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and biochemical analysis of the size-dependent nanoimmunoresponse in mouse Peyer's patches using fluorescent organosilica particles

Abstract: Background/objective The size-dependent mucosal immunoresponse against nanomaterials (nanoimmunoresponse) is an important approach for mucosal vaccination. In the present work, the size-dependent nanoimmunoresponse of mouse Peyer’s patches (PPs) and immunoglobulin A (IgA) level was investigated using fluorescent thiol-organosilica particles. Methods Various sizes of fluorescent thiol-organosilica particles (100, 180, 365, 745, and 925 nm in diameter) were administered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…These immunohistological studies indicate that the colocalization ratios of F140 and each macrophage surface marker were different. Previously, we reported differences in particle uptake of macrophage surface markers as well as particle size in mouse Peyer’s patches using CD11b 10 and in mouse spleens using CD169 and F4/80 . These studies showed that macrophages with the same surface markers also exhibited differences in particle uptake, indicating that macrophages with the same markers can be further classified according to particle uptake.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These immunohistological studies indicate that the colocalization ratios of F140 and each macrophage surface marker were different. Previously, we reported differences in particle uptake of macrophage surface markers as well as particle size in mouse Peyer’s patches using CD11b 10 and in mouse spleens using CD169 and F4/80 . These studies showed that macrophages with the same surface markers also exhibited differences in particle uptake, indicating that macrophages with the same markers can be further classified according to particle uptake.…”
Section: Resultsmentioning
confidence: 90%
“…Previously, we reported differences in particle uptake of macrophage surface markers as well as particle size in mouse Peyer's patches using CD11b 10 and in mouse spleens using CD169 and F4/80. 11 These studies showed that macrophages with the same surface markers also exhibited differences in particle uptake, indicating that macrophages with the same markers can be further classified according to particle uptake. Classification of macrophages using particle uptake is a new approach.…”
Section: Immunohistochemical Study Using Antibodies Against Macrophag...mentioning
confidence: 92%
See 1 more Smart Citation
“…To date, many methods have been developed for micronizing such particles [ 5 , 6 ]. In addition to improving the solubility of the drug due to an increase in the drug particle’s surface area, drugs micronized to the nano-order may also be directly delivered through intestinal Peyer’s patches [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organosilica NPs can contain not only functional molecules such as fluorescent dye 20 , 21 but also nanomaterials 22 , 23 . Functionalized organosilica particles were applied for biomedical research such as imaging in vitro 20 , 22 and in vivo 21 25 , and single cell analysis 26 , 27 . In addition functional molecules and nanomaterials could show new function in organosilica nanoparticles 21 – 23 .…”
Section: Introductionmentioning
confidence: 99%